Social capital of directors and corporate governance: A social network analysis - NIU, Zihan (Institutional Knowledge at Singapore Management University, 2017)
This Article examines how a director’s social capital might affect his or her behavior, the board’s performance, and corporate governance, as well as the potential normative implications of the director’s social network. We argue that the quality of board performance could be improved where the social network closure within the board is high and there are many non-redundant contacts beyond the board. Network closure can improve trust and collaboration within a board, while external contacts may benefit a company with more diverse sources of information. Moreover, different network positioning leads to the inequality of social capital for directors. With more social capital, a director is more likely to be powerful and influential on the other directors on the board. Regarding the fulfillment of their monitory function, we suggest that independent directors would be unlikely to compromise their monitory liability when they have more social capital on the board than the managerial directors. We demonstrate our theory with an analysis of corporate boards of companies listed in Hong Kong. Although it is not easy to incorporate social network analysis into legislation or corporate governance code, our theory may further the understanding of the function and effectiveness of different board structures and provide some insights into the future selection of directors by a company within an existing legal framework.